Pulverized coal selective oxidation modification method for ultralow nitrogen emission of fire coal
Through the coal powder selective oxidation modification method, mechanical force chemical coupled selective oxidation technology is used to regulate the molecular configuration of coal powder, which solves the problem of difficult reduction of coal-fired NOx emissions and achieves ultra-low emissions of NOx.
Patent Information
- Application Number
- CN202411707720.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to effectively reduce NOx emissions during coal burning by directly starting from the coal itself, and the system is complex and cumbersome.
The coal powder selective oxidation modification method is adopted, and the coal powder molecular configuration is directionally regulated through mechanical force chemical coupling selective oxidation technology, and the generation path of NOx precursor during thermal conversion is changed, thereby reducing the release of NOx.
The release amount of NOx gas is significantly reduced, and the ultra-low emission of NOx is achieved. The method is simple and the system is not complicated.
Smart Images

Figure CN119432465A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal, and in particular relates to a method for selective oxidation modification of pulverized coal for ultra-low nitrogen emission of coal combustion. Background Art
[0002] The basic characteristics of my country's energy structure are "rich in coal, poor in oil, and little gas". Fossil fuels, especially coal resources, have always been my country's main energy and important raw materials. According to the data in the World Energy Statistical Yearbook released in 2024, China is the world's largest coal demander, accounting for 56% of the world, and coal accounts for 55.3% of China's energy structure, indicating that coal will continue to be the main energy source for China's development in the future.
[0003] Nitrogen oxides (NO x ) is one of the main pollutants produced in the process of coal combustion. x Ultra-low emissions are an urgent need for my country's economic and environmental sustainable development. Coal molecular configuration mainly includes functional groups, pore structure and microcrystalline morphology. These key microscopic physicochemical properties can change the thermal conversion process of NO x The generation pathway of precursors, which in turn affects NO x Selective oxidation of coal can regulate its molecular configuration in a directional manner, but current research mainly focuses on the extraction, gasification and liquefaction of coal, and has not yet revealed the migration of fuel nitrogen in coal after selective pretreatment and its effect on NO x The impact of emissions.
[0004] Existing technologies for controlling nitrogen emissions from coal combustion are often limited to systematic combustion process control technologies such as staged combustion and flue gas circulation, combined with catalytic reduction tail flue gas treatment technologies, etc. These technologies require multi-step treatment during combustion, with cumbersome steps and complex systems. No research has directly tried to reduce nitrogen emissions from coal itself. Therefore, a new coal powder modification technology has been developed to regulate the molecular morphology and structure by introducing modification, thereby promoting NO during combustion. x The goal of homogeneous and heterogeneous reduction is to achieve NO x Ultra-low emissions are an urgent problem to be solved in this field.
[0005] Selective oxidation, also known as partial oxidation, refers to the process in which a few carbon atoms (or hydrogen atoms) react with the oxidant in hydrocarbons and their derivatives, while the remaining carbon atoms (or hydrogen atoms) do not react with the oxidant. The oxygen-containing groups introduced by selective oxidation can attack CC or C=C bonds in thermochemical reactions, releasing more active sites and free radicals. In addition, the introduction of oxygen-containing functional groups around fuel nitrogen can change the local electron cloud distribution of nitrogen-containing heterocycles in coal, thereby reducing the CN bond energy and changing the conversion path of fuel nitrogen in thermochemical processes. This provides conditions for clarifying the migration path of nitrogen from the perspective of the local microenvironment. When negatively charged oxidant ions combine with the interlayer carbon skeleton, interlayer compounds are formed without destroying the basic structural units of the carbon skeleton. The rapid decomposition of these interlayer compounds at high temperatures accelerates the evolution of pore structure and microcrystalline morphology. Therefore, the use of selective oxidation to directionally regulate the local microenvironment around fuel nitrogen and the molecular configuration of coke helps to clarify the influence of the local microenvironment and molecular configuration on the nitrogen migration path during thermal conversion from a global perspective, thereby promoting ultra-low NO x Development of combustion technology. Summary of the invention
[0006] In view of the shortcomings of the existing coal combustion nitrogen emission control technology, the present invention proposes a coal powder selective oxidation modification method for ultra-low nitrogen emission of coal combustion. Starting from the coal itself, the directional regulation of the coal powder molecular configuration is achieved through the method of mechanical force chemical coupling chemical reagent selective oxidation modification, thereby controlling NO in the combustion process. x emissions, achieving the goal of ultra-low nitrogen emissions.
[0007] The present invention adopts the following technical solutions to achieve this: the molecular configuration of coal mainly includes functional groups, pore structure and microcrystalline morphology, etc. These key microscopic physical and chemical properties can change the NO x The generation pathway of precursors, which in turn affects NO x The mechanical force chemical coupling selective oxidation technology is used to directionally regulate the local microenvironment around the fuel nitrogen and the molecular configuration of coke. Due to the mechanical force collision and extrusion during the coal powder pulverization process, the structural deformation is caused, and a series of active oxidative species with lower bond energy produced by the oxidant can promote the grafting of oxygen-containing functional groups on hydrocarbon substances. Therefore, the molecular structure of the coal powder after selective oxidation modification changes, which promotes NO x Homogeneous and heterogeneous reduction of molecules can significantly reduce NO x The amount of gas released.
[0008] In one aspect, the present invention provides a method for selective oxidation modification of coal powder, comprising the following steps:
[0009] Step 1: Use crushing equipment to crush and grind the raw coal and perform mechanical and chemical modification on the coal powder;
[0010] Step 2: selectively oxidize and modify the pulverized coal treated in step 1 to obtain modified pulverized coal.
[0011] In some embodiments, the raw coal is selected from different coal ranks such as lignite, bituminous coal, anthracite, etc. as the application object.
[0012] In some embodiments, in step one, the pulverizing equipment includes but is not limited to a ball mill, a hammer mill, a jaw crusher, a roller mill, a shearing mill, a vibration mill, an air flow mill and the like.
[0013] In some embodiments, in step one, when the coal powder is pulverized by mechanical force, deformation or stress is generated in the molecular or crystal structure by means of grinding, extrusion, shearing or friction, thereby resulting in energy accumulation and breaking or reorganization of chemical bonds. Mechanochemistry is widely used due to its advantages such as solvent-free operation, low energy consumption, and unique reaction pathway.
[0014] In some embodiments, in step 1, the ground coal powder is directly collected without any screening, so as to avoid the influence of component segregation as much as possible.
[0015] In some embodiments, in step 1, during the coal powder grinding process, adding appropriate additives can promote oxidation modification, and common additives include potassium permanganate, sodium hypochlorite, chromium oxide, ammonium persulfate and other reagents. The addition ratio of potassium permanganate to coal powder is 1:10-1:5, the addition ratio of potassium hypochlorite to coal powder is 1:10-1:3, the addition ratio of chromium oxide to coal powder is 1:20-1:5, and the addition ratio of ammonium persulfate to coal powder is 1:10-1:2, preferably 1:10-1:5.
[0016] In some embodiments, the particle size distribution of the coal powder after the treatment in step 1 is tested using a laser particle size analyzer to obtain a particle size distribution curve of the coal powder, including key particle size values such as D10, D50, and D90, which reflects the proportion of particles of different particle sizes in the coal powder. Coal powder with smaller particle size usually has a higher specific surface area, which can improve the reaction activity during the combustion process. And uniform particle size distribution usually helps to improve the fluidity of coal powder. Preferably, the coal powder particle size is controlled within the range of 14-24 μm by mechanochemical modification.
[0017] In some embodiments, the shape of the coal powder particles, such as circularity and aspect ratio, can be evaluated by the image analysis function of the particle size analyzer. The shape of the coal powder particles will affect the fluidity of the coal powder.
[0018] In some embodiments, due to the influence of mechanochemistry and additives during grinding, the industrial analysis and elemental analysis of coal with different particle sizes change, and the coal powder with sufficient grinding and longer mechanochemical action time has a higher oxygen content.
[0019] In some embodiments, in step 2, the coal powder is selectively oxidized and modified using an oxidant, wherein the oxidant is H2O2 with a mass concentration of 1-10%, peracetic acid (PAA), nitric acid with a mass concentration of 10-30%, or a peroxydisulfate solution with a molar concentration of 0.01-0.1 mol / L. Furthermore, the ratio of the coal powder to the oxidant is 1g:10ml-1g:50ml.
[0020] In some embodiments, in step 2, the selective oxidation modification comprises the following steps: mixing coal powder and an oxidant in a container, stirring and reacting under heating, washing and drying the oxidized coal powder to obtain modified coal powder. Preferably, the coal powder and the oxidant are stirred at 30-50°C for 4-8 hours. Preferably, the oxidized coal is washed with deionized water until the filtrate after washing is colorless. Preferably, the washed coal powder is dried at 80-120°C for 6-24 hours.
[0021] In some embodiments, in step 2, H2O2 and peracetic acid (PAA) are preferably used as oxidants, which are inexpensive and the additional products after the oxidation reaction will not harm the environment. In addition, since the oxidation reaction of peracetic acid and H2O2 is thermally feasible, a series of active oxidation species with lower bond energy can be generated, thereby promoting the grafting of oxygen-containing functional groups on hydrocarbon substances. At the same time, during the oxidation process of H2O2 or peracetic acid, the deposition of insoluble chemicals on the particle surface can also be avoided.
[0022] In some embodiments, in step 2, the coal powder oxidation method also includes gas phase oxidation method, liquid phase oxidation method, plasma oxidation method, biological oxidation method, etc.
[0023] In a second aspect, the present invention provides modified coal powder obtained by the above method.
[0024] In some embodiments, the modified coal powder reduces NO emission by more than 30% compared to raw coal.
[0025] Beneficial Effects
[0026] 1. The selective oxidation modification method of coal powder of the present invention realizes the directional regulation of the molecular configuration of coal powder: the pore structure evolves, oxidation causes the ratio of smaller pores to larger pores to change, and the average pore radius to change; the crystallite parameters evolve, the standard deviation of the adjacent distribution of the first layer of carbon atoms (σ1), the average aromatic layer width (L a ), average stack height (L c), the average number of stacked layers ( <n>), the average interlayer gap (a3), the standard deviation of the aromatic interlayer gap (σ3), and the orientation parameter (q) will all change due to selective oxidation.
[0027] 2. The selective oxidation modification method of pulverized coal of the present invention realizes the directional regulation of the conversion path of NH3 and HCN: HCN and NH3 are used as NO x The key precursor generated can react with oxygen or oxygen-containing groups to generate NO x The HCN conversion rate of oxidized coal is higher than that of raw coal, and the NH3 conversion rate is significantly improved; the HCN conversion rate decreases with the increase of particle size, while the NH3 conversion rate increases with the increase of particle size.
[0028] 3. The coal powder selective oxidation modification method of the present invention realizes the control of NO x Directional regulation of generation: The total conversion rate of fuel nitrogen from all oxidized coals to NH3 and HCN is much greater than that of raw coal, and the conversion reaction of NH3 and HCN to NO is more intense. x The homogeneous and heterogeneous generation processes of NO do not dominate. x Compared with the original coal, the homogeneous reduction amount increased, the heterogeneous reduction effect decreased, the homogeneous and heterogeneous synergistic reduction increased, and the total NO x The reduction amount is greater than the total reduction amount of the raw coal. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The figure shows the change of the pore ratio of raw coal and oxidized coal with the particle size in Example 1 of the present invention, wherein: Figure 1 (a)-(d) are the graphs of the proportion of smaller pores in Henan coal changing with particle size, the graphs of the proportion of larger pores in Henan coal changing with particle size, the graphs of the proportion of smaller pores in Inner Mongolia coal changing with particle size, and the graphs of the proportion of larger pores in Inner Mongolia coal changing with particle size;
[0030] Figure 2 The graph showing the average pore radius of Henan coal and Inner Mongolia coal as a function of particle size (nm) is shown;
[0031] Figure 3 The conversion rate of fuel nitrogen into NH3 and HCN in Example 1 of the present invention is shown, wherein: Figure 3 (a)-(d) are the conversion rates of Henan coal fuel nitrogen into NH3, Henan coal fuel nitrogen into HCN, Inner Mongolia coal fuel nitrogen into NH3, and Inner Mongolia coal fuel nitrogen into HCN, respectively;
[0032] Figure 4 The emission of NO during the combustion process in Example 1 of the present invention is shown, wherein: Figure 4 The NO emissions during the combustion of Henan coal (left) and Inner Mongolia coal (right) are shown respectively. DETAILED DESCRIPTION
[0033] The following describes the preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0034] In a preferred embodiment, the method for selective oxidation modification of pulverized coal of the present invention comprises the following steps:
[0035] Use a pulverizing device to grind 100-300g of raw coal, use a laser particle size analyzer to test the particle size distribution of the coal powder, and perform industrial analysis and elemental analysis on the ground coal powder;
[0036] The ground coal powder is selectively oxidized and modified, and H2O2 or PAA solution with a mass concentration of 1-10% is used as an oxidant. The raw coal is dried at 80-120°C for 6-24 hours before oxidation; each raw coal and oxidant are mixed in a container at a ratio of 1g:10ml-1g:50ml; the container is placed in a water bath with magnetic stirring, and stirred at 30-50°C for 4-8 hours to obtain oxidized coal; the oxidized coal is washed with deionized water until the washed filtrate is colorless; finally, the oxidized coal is dried at 80-120°C for 6-24 hours.
[0037] Example 1
[0038] High-volatile Inner Mongolia bituminous coal and low-volatile Henan anthracite were selected.
[0039] Use a high-energy ball mill (Germany Retsch PM100) to grind it in air atmosphere. Weigh about 150g of raw coal into a grinding jar (500ml), add 1 / 3 volume of φ20mm grinding balls into the grinding jar. Then, set the grinding rate from 300rpm / min to 500rpm / min.
[0040] The Malvern MAM5004 laser particle size analyzer (UK) was used to test the particle size distribution of coal powder. The average particle sizes of Inner Mongolia coal were 21.6 μm, 18.7 μm, 13.6 μm and 11.0 μm, and the average particle sizes of Henan coal were 34.7 μm, 23.9 μm, 14.1 μm and 8.1 μm.
[0041] In order to avoid the influence of component segregation as much as possible, the ground coal powder is directly collected without any screening.
[0042] Henan anthracite and Inner Mongolia bituminous coal were selectively oxidized using 5% mass concentration H2O2 and peracetic acid (PAA) solutions, respectively.
[0043] The raw coal was dried at 105°C for 12 hours before oxidation. The raw coal and the oxidant were mixed in a beaker at a ratio of 1g:30ml. The beaker was placed in a water bath with magnetic stirring and stirred at 40°C for 6 hours. The oxidized coal was washed with deionized water until the filtrate after washing was colorless. Finally, the oxidized coal sample was dried at 105°C for 12 hours to obtain oxidized coal powder.
[0044] The particle size distribution of coal powder can be obtained by using a laser particle size analyzer. The coal sample crushing effect and coal powder reactivity can be evaluated by the average particle size distribution characteristics of coal powder. The fluidity of coal powder can be evaluated by the particle shape.
[0045] The ground coal powder is subjected to industrial analysis and elemental analysis. The combustion efficiency and calorific value of the coal powder are evaluated by industrial analysis, and the combustion characteristics and pollutant emissions of the coal powder are evaluated by elemental analysis.
[0046] The oxidation effect is evaluated by the oxygen content of the pulverized coal after oxidation, and the reaction performance is evaluated by parameters such as the distribution of oxygen-containing functional groups and specific surface area.
[0047] After mechanical crushing and selective oxidation, the modified coal powder undergoes the following changes:
[0048] 1. Pore structure evolution: During the ultrafine grinding process, micropores increase and mesopores decrease. For oxidized coal, PAA oxidation promotes the formation of mesopores, the proportion of smaller pores decreases and the proportion of larger pores increases, such as Figure 1 As shown in (a)-(d). Figure 1 (a)-(d) are respectively the graphs of the proportion of smaller pores in Henan coal as a function of particle size, the graph of the proportion of larger pores in Henan coal as a function of particle size, the graph of the proportion of smaller pores in Inner Mongolia coal as a function of particle size, and the graph of the proportion of larger pores in Inner Mongolia coal as a function of particle size. It can be seen from the figure that with the decrease of particle size, the proportion of smaller pores shows a downward trend; the proportion of smaller pores in PAA-oxidized coal decreases while the proportion of larger pores increases, while the change in H2O2-oxidized coal is not obvious; the proportion of larger pores in Henan raw coal (HN) and H2O2-oxidized Henan coal (HN_hp) is greater than that in the corresponding Inner Mongolia coal (NMG) and H2O2-oxidized Inner Mongolia coal (NMG_hp); the proportion of smaller pores in PAA-oxidized Henan coal (HN_pa) is higher than that in the corresponding PAA-oxidized Inner Mongolia coal (NMG_pa). Figure 1 As shown in (b) and (d), the proportion of larger pores in Henan anthracite (HN) is higher than that in the corresponding Inner Mongolia bituminous coal (NMG). Figure 2 (a)-(b) are the average pore radius of Henan coal and Inner Mongolia coal, respectively. It can be seen from the figure that the average pore diameter decreases with the increase of particle size.
[0049] 2. Crystallite morphology evolution: In the present invention, σ1, L a , L c , a3, σ3, and q will all evolve in a directed manner with the action of mechanochemistry and selective oxidation, and the specific evolution rules are as follows.
[0050] Evolution of the standard deviation (σ1) of the adjacent distribution of the first layer of carbon atoms: During the ultrafine grinding process, σ1 shows a downward trend as the particle size decreases. In general, the σ1 of large-particle Inner Mongolia raw coal and Inner Mongolia oxidized coal is greater than the corresponding Henan coal. However, the σ1 of small-particle Inner Mongolia coal is smaller than the corresponding Henan coal. During the oxidation process, the σ1 of large-particle Inner Mongolia oxidized coal is smaller than that of Inner Mongolia raw coal, and the σ1 of small-particle Inner Mongolia raw coal is smaller than that of Inner Mongolia oxidized coal. The σ1 of H2O2-oxidized Henan coal is slightly smaller than that of Henan raw coal, the σ1 of small-particle PAA-oxidized Henan coal is lower than that of raw coal, and the σ1 of large-particle PAA-oxidized Henan coal increases.
[0051] Average aromatic layer width (L a ) and average stack height (L c ) evolution: In the ultra-fine grinding process, the large particle size L c Reduce, small particle size L a During the oxidation process, the L a Lower than that of Inner Mongolia raw coal. a Slightly larger than Henan raw coal, small particle size Henan oxidized coal L a Lower than Henan raw coal. The L c Compared with the original coal, the L c Less than Henan coal oxidized by H2O2.
[0052] Evolution of average interlayer gap (a3): During the ultrafine grinding process, a3 shows a downward trend as the particle size decreases. During the oxidation process, the a3 of Inner Mongolia oxidized coal is smaller than the corresponding Inner Mongolia raw coal. The a3 value of Inner Mongolia coal oxidized by H2O2 is lower than that of Inner Mongolia coal oxidized by PAA. The a3 of Henan coal oxidized by PAA is slightly smaller than that of Henan coal oxidized by H2O2. The a3 of Henan oxidized coal is greater than that of Henan raw coal.
[0053] Standard deviation of aromatic layer gap (σ3): During the ultrafine grinding process, σ3 decreases as the particle size decreases. During the oxidation process, the σ3 of oxidized coal from Henan and Inner Mongolia is greater than that of the corresponding raw coal.
[0054] Orientation parameter (q): During the ultrafine grinding process, q shows a downward trend as the particle size decreases. During the oxidation process, the q value of Inner Mongolia oxidized coal is generally larger than that of Inner Mongolia raw coal. The q value of Henan coal oxidized by H2O2 is larger than that of Henan raw coal. The q value of Henan coal oxidized by large-particle PAA is lower than that of Henan raw coal, and the q value of Henan coal oxidized by small-particle PAA gradually exceeds that of Henan raw coal.
[0055] 3. Correlation between oxidized coal crystal morphology and pore structure: For smaller pores, L a , σ1, a3 and σ3 show large correlation coefficients and are the main influencing factors for the evolution of smaller pores. c , <n>, a3 and σ3 significantly affect the larger pores, that is, the smaller pores are affected by both the single-layer structure and the layer stacking characteristics, while the larger pores are mainly affected by the layer stacking characteristics.
[0056] 4. Effect of selective oxidation on the conversion pathways of NH3 and HCN:
[0057] (1) The influence of specific functional groups and free radicals: Figure 3 As shown in (a)-(d), the NH3 conversion rate of H2O2 oxidized coal is significantly higher than that of the corresponding raw coal, and the HCN conversion rate of H2O2 oxidized coal increases slightly. The HCN conversion rate of PAA oxidized coal increases significantly relative to the raw coal, the NH3 conversion rate of small-particle PAA oxidized coal generally decreases, and the NH3 conversion rate of large-particle PAA oxidized coal increases. The conversion rate of Henan coal fuel nitrogen into NH3 and HCN is generally lower than that of the corresponding Inner Mongolia coal. The conversion rate of fuel nitrogen into NH3 and HCN increases with decreasing particle size. Figure 3 As shown in (b) and (d), the HCN conversion rate of oxidized coal increases with the decrease of particle size. Figure 3 As shown in (a) and (c), the NH3 conversion rate of all oxidized coals decreases with the decrease of particle size. The conversion of HCN to NH3 in large-particle oxidized coal is more intense, resulting in an increase in the NH3 conversion rate in large-particle oxidized coal.
[0058] (2) Influence of pore structure and crystallite morphology: Coal molecular configuration mainly includes pore structure and crystallite morphology, which are closely related to the conversion process of HCN and NH3. In general, the layer stacking characteristics of particles with different particle sizes show a stronger correlation with the NH3 and HCN conversion rates of all coals. The HCN conversion rate of all coals and the NH3 conversion rate of the two raw coals decrease with increasing particle size. For all oxidized coals, the weakening of NH3 adsorption in large-particle oxidized coal leads to an increase in NH3 conversion rate with increasing particle size.
[0059] (3) Effect of local microenvironment on the conversion of NH3 and HCN: For H2O2 oxidized coal, the combination of -NH2 and H radicals dominates the increase of NH3 in the oxidized coal pyrolysis process. For PAA oxidized coal, the H migration process is accompanied by the formation of HCN. With the increase of oxidized coal particle size, the introduced COOH is significantly reduced, resulting in a decrease in HCN. The capture capacity of HCN by reaction defects within the particles is enhanced, reducing the release of HCN in large particles. Under conditions rich in oxygen-containing functional groups, the adsorption energy of HCN at the reaction sites is lower than that of NH3, and the release of NH3 increases with the increase of particle size.
[0060] 5. Effect of selective oxidation on NO release characteristics: NO release characteristics can be divided into NO homogeneous and heterogeneous generation characteristics and reduction characteristics and considered separately.
[0061] (1) Characteristics of homogeneous and heterogeneous formation of NO: HCN and NH3 are important gas-phase intermediates in the generation of NO from the combustion of coke nitrogen. The total conversion rate of all oxidized coals is much greater than that of raw coal. Based on the homogeneous and heterogeneous formation mechanism of NO, all released NH3 and HCN will be completely oxidized to NO during the combustion process. The conversion reaction of NH3 and HCN to NO during the combustion of oxidized coal is more intense. The homogeneous and heterogeneous formation process of NO during the combustion of oxidized coal does not dominate the total NO emissions.
[0062] (2) Characteristics of homogeneous and heterogeneous reduction of NO: In addition to the homogeneous and heterogeneous generation of NO, NO emissions during coal combustion are also affected by homogeneous and heterogeneous reduction. The total release of NH3 and HCN during the pyrolysis of raw coal is much lower than that of oxidized coal. In fact, the combustion process of raw coal releases more NO than the corresponding oxidized coal, and the heterogeneous reduction of NO by pure coke does not play a dominant role in the total NO emissions from oxidized coal combustion. From the perspective of oxidation, compared with raw coal, H2O2 oxidized coal slightly increases HCN, and PAA oxidized coal significantly promotes the generation of HCN. From the perspective of particle size, HCN in large particles shows a downward trend with the increase of particle size. Under oxygen-deficient conditions, the heterogeneous reduction involving HCN dominates the total generation of NO during the combustion of oxidized coal. The heterogeneous reduction process of coke with the participation of NH3 is not a dominant factor in the total NO emissions.
[0063] (3) Decoupled reduction characteristics of NO in homogeneous and heterogeneous phases: The contribution of the interaction between homogeneous and heterogeneous reduction to NO reduction can be qualitatively obtained by subtracting the homogeneous and heterogeneous reduction of NO in the decoupled experiment from the total NO reduction in the direct reduction experiment. Figure 4 The NO emissions during the combustion of Henan coal (left) and Inner Mongolia coal (right) are shown. It can be seen from the figure that the NO emissions of coal oxidized by PAA decreased significantly, the NO emissions of Henan coal oxidized by H2O2 decreased significantly, but the NO emissions of Inner Mongolia coal oxidized by H2O2 decreased slightly. Figure 4 As shown in the figure, for the two types of coal, the homogeneous reduction of NO after oxidation modification increased compared with the original coal, and the heterogeneous reduction of NO decreased significantly after oxidation. The total NO reduction of all oxidized coals was greater than the total reduction of the corresponding original coal. For the same type of coal, it can be observed that a greater HCN conversion rate corresponds to a greater NO interactive reduction, accompanied by lower NO emissions, which also indicates that the heterogeneous reduction reaction involving HCN under local oxygen-deficient conditions dominates the difference in total NO generation between original coal and oxidized coal.
[0064] Therefore, by selectively oxidizing raw coal, NO in the combustion products can be effectively controlled. x Emissions, combined Figure 3 and Figure 4 It can be seen that, especially when the raw coal grinding particle size is controlled within the intermediate particle size range of 14-24μm, after oxidation modification, it is more conducive to the conversion of fuel nitrogen into NH3 and HCN and the reduction of NO emissions, and is expected to form a new type of high-efficiency and low-cost low-nitrogen combustion technology.
[0065] In this embodiment, for Henan coal, it was found that NO could be reduced by 31.72% at most after selective oxidation; for Inner Mongolia coal, it was found that NO could be reduced by 34.30% at most after selective oxidation.
[0066] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.< / n> < / n>
Claims
1. A method for selective oxidation modification of coal powder, comprising the following steps: Step 1: Use crushing equipment to crush and grind the raw coal and perform mechanical and chemical modification on the coal powder; Step 2: selectively oxidize and modify the pulverized coal treated in step 1 to obtain modified pulverized coal.
2. The method for selective oxidation modification of pulverized coal according to claim 1, wherein: The raw coal is selected from lignite, bituminous coal and anthracite.
3. The method for selective oxidation modification of pulverized coal according to claim 1, wherein: The pulverizing equipment is selected from a ball mill, a hammer mill, a jaw crusher, a roller mill, a shearing mill, a vibration mill, and a jet mill.
4. The method for selective oxidation modification of pulverized coal according to claim 1, wherein: In step one, during the coal powder grinding process, an additive is added, wherein the additive is selected from potassium permanganate, sodium hypochlorite, chromium oxide, and ammonium persulfate.
5. The method for selective oxidation modification of pulverized coal according to claim 1, wherein: In step one, the coal powder particle size is controlled within the range of 14-24 μm through mechanochemical modification.
6. The method for selective oxidation modification of pulverized coal according to claim 1, wherein: In step 2, the pulverized coal is selectively oxidized and modified using an oxidant, wherein the oxidant is H2O2 with a mass concentration of 1-10%, peracetic acid (PAA), nitric acid with a mass concentration of 10-30%, or a peroxydisulfate solution with a molar concentration of 0.01-0.1 mol / L.
7. The method for selective oxidation modification of pulverized coal according to claim 6, wherein: The ratio of coal powder to oxidant is 1g:10ml-1g:50ml.
8. The method for selective oxidation modification of pulverized coal according to claim 6, wherein: In step 2, the selective oxidation modification includes the following steps: mixing coal powder and an oxidant in a container, stirring and reacting under heating, and washing and drying the oxidized coal powder to obtain modified coal powder.
9. The method for selective oxidation modification of pulverized coal according to claim 8, wherein: The coal powder and the oxidant are stirred at 30-50°C for 4-8 hours.
10. Modified coal powder obtained by the coal powder selective oxidation modification method according to any one of claims 1 to 9.